CO₂ Emissions in the Visegrad Group Countries and the European Union Climate Policy - Dorota Wawrzyniak (Comparative Economic Research. Central and Eastern Europe, 2020)
Climate change isone ofthe most pressing challenges ofour time and several policies trying tomitigate this negative phenomenon have been implemented. The reduction ofGHG emissions along with the improvement inenergy efficiency and the increase inthe share ofenergy consumption from renewable sources also constitute the Euro-pean Union policy priority. Inthis context, the aim ofthis article isto explore factors that affect changes inCO2 emissions inthe four EU member states that form the Visegrad Group, during the period 1993-2016. The analysis was conducted using the Logarithmic Mean Divisia Index (LMDI) decomposition method and the Kaya iden-tity, which enables the factors contributing most tothe CO2 emissions changes tobe identified. Italso allows the results tobe discussed inrelation tothe European Union's climate policy.According tothe decomposition analysis results, energy intensity and economic growth measured interms ofGDP per capita were the main factors driving chang-es inCO2 emissions across all countries considered. The emissions decrease result-ed mainly from animprovement inenergy efficiency and toalesser extent from the change inthe energy mix towards renewables.
Keywords: Q50; Q54; 330; carbon dioxide emissions; LMDI decomposition analysis; the European Union climate policy; Visegrad Group countries